Bonding methods for chip integration with Parylene devices. (19th February 2021) - Yoo, James; Meng, Ellis
Abstract: Flexible electronics require more compact interconnects for next-generation devices. Polymer devices can be bonded to integrated circuit chips, but combining flexible and rigid substrates poses unique technical challenges. Existing technologies either cannot achieve the density required for modern chips or employ specialized equipment and complex processes to do so. Here, we adapt several approaches to achieve fine-pitch bonding between rigid and flexible substrates including epoxy, ultrasonic wire, and anisotropic conductive film bonding and also introduce a novel technique called polymer ultrasonic on bump (PUB) bonding. Using Parylene C devices and various rigid substrates as our model testbed systems, we investigate these four methods across a range of bond pad size and pitch by measuring yield and resistance and by subjecting devices to thermomechanical reliability tests. We demonstrate that all methods are capable of bonding fine pitch interconnects (100 µ m) at low temperature (<100 °C). Additionally, we focus on PUB bonding and join a packaged chip and a bare die to Parylene devices.